Pemberdayaan Peran Kader Dalam Pencegahan Stunting Dengan Penyuluhan Gizi Di Desa Menampu - Istifadatul Ilmiya; Nurul Aini; Januar Putri Wayanshakty (Poltekkes Kemenkes Surakarta, 2025)
Background: Stunting is a condition of growth failure in children that can be caused by chronic malnutrition so that children are too short for their age, which is at risk of increased morbidity and mortality, decreased immune system and increased risk of infection. The prevalence of stunting in Indonesia in 2023 is 15.8%, in East Java 13.8% and in Jember 29.7%. This community service activity aims to improve the ability of cadres as educators in reducing the incidence of stunting in organizing posyandu activities. Methods: The activities were carried out in Menampu Village in December 2024 targeting the posyandu cadres. This included the distribution of questionnaires, education on stunting, and practice in determining nutritional status. An evaluation was conducted to assess the improvement in the knowledge and skills of the cadres. Results: The results of the activity showed an increase in cadre knowledge related to stunting, most of which were in the good category (73.33%) and there was an increase in cadre skills in the correct category (100%) in determining nutritional status. Conclusion: Knowledge about stunting and skills to determine nutritional status improved after the counseling and training sessions. It is recommended to have periodic follow-ups and to expand the program to other villages for the prevention of stunting.